The Output-Inflation Nexus in Ukraine : Is there a Trade-Off? - Ghosh, Atish (Washington, D.C. : International Monetary Fund, 1996)
This paper examines whether expansionary credit policy can help sustain output growth in transition economies, with particular reference to Ukraine's experience since 1992. We find that, while real credit growth is indeed associated with higher output growth, an increase in the growth rate of nominal credit does not, in general equilibrium, stimulate output growth. Following a short-lived boom - caused by falling real wages - the increase in the growth rate of nominal credit leads to a decline in the level of output.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet